PROSTHETIC REQUIREMENTS IN PERIODONTAL PROPHYLAXIS - Kamel Earar; Mădălina Nicoleta Matei; Sergiu Focşăneanu; Constanţa Mocanu (Romanian Society of Oral Rehabilitation, 2014)
The purpose of this paper is to identify and analyze the shortcomings of achieving gnatho prosthetic devices and their detrimental effect on periodontal health, and the periodontal protection methods employed in the technological algorithm applied for fixed gnatho prosthetic devices. Material and methods To achieve periodontal prophylaxis, we analyzed the compliance in clinical and technological process of a series of technical requirements for rebuilding morpho- functional integrity of the dental arch by bridges. Results To achieve periodontal prophylaxis should be pursued during clinical and technological procedures the following: respect of coronary morphology, restoring the contour and position of contact areas, inter proximal embrasures restoration, restoration of the physiological contours of the buccal and lingual surfaces, the correct reproduction of natural cemento-enamel junction on mesial and distal faces, respect of gingival sulcus area, achieving perfect adaptation of the margins of restorations, periodontal protection in sub-sulcular area, achieving the profile of emergence. Conclusions By respecting these the principles, are ensured both restoration longevity and periodontal health.